Factors which influence sustainable implementation of corporate governance systems in an institution of higher learning - Assan, T.E.B. (South African Journal of Higher Education, 2021)
As the demand for higher education continues to grow and as governments acknowledge their role in promoting economic development, it becomes increasingly important to ensure that higher education systems are managed in an effective way. The study examined the factors which influence effective and sustainable corporate governance in a merged University. The study was intended to create awareness of the challenges and opportunities regarding perceived conflicts in a new institution of Higher Learning with respect to management of transformation in higher education A mixed method approach was used and, as a result, data were collected using a questionnaire and interview instruments. The sample was made up of 120 randomly selected staff and students. The research established that issues of language and culture, effective communication as well as stakeholders’ consultations among others are factors which influence effective corporate governance. The study recommended that more should be done to improve the culture, ethos and the practices that would enhance a sustainable corporate governance system.